Comparison of Accident Databases and Analysis of Past Industrial Accidents in the Chemical Process Industry - Arun, P. A.; Tauseef, S. M.; Uniyal, U. (Engineering, Technology & Applied Science Research, 2022)
Despite India being home to some of the worst chemical industry disasters, there is no proper accident reporting and analysis mechanism. The National Informatics Centre of the Ministry of Environment and Forest (MoEF) presented an online accident database called CAIRS to assist Past Accident Analysis (PAA). This paper compares CAIRS with major accident databases widely used by safety professionals. The parameters considered for compassion are scope, accessibility, method of data collection, quality, and the frequency of reporting. Past accident analysis showed that the total number of reported events is more or less steady and the number of major accidents is decreasing marginally in European countries, whereas in India only a few states report accidents using the CAIRS platform. The analysis raised serious concerns about the monitoring of reported information in the Indian database. At present, the information available in this database is not reliable and any conclusion based on this information can be misleading. Suggestions are offered to enhance the efficacy of the Indian accident database.